Legal Force of Evidence in Court Against Landowners Acting in Good Faith with Letter C Evidence Above Which Another Party's Certificate of Ownership is Issued - Graha, Kahfi Purwana; Artaji, Artaji; Rubiati, Betty (Universitas Islam Sultan Agung, 2025)
The Basic Agrarian Law stipulates that land ownership rights can be inherited from generation to generation. One of the main objectives of the Basic Agrarian Law is to provide legal certainty regarding land rights for all citizens. However, many problems are still found related to Letter C, where land registered with Letter C is actually issued a certificate of ownership in the name of another party. This condition creates legal uncertainty for Letter C holders, because in judicial practice there are differences in legal considerations between decisions. Some decisions grant claims for ownership disputes filed by Letter C holders, while other decisions reject similar claims. The purpose of this study is to identify and analyze the legal force of evidence in court against landowners who act in good faith with evidence of Letter C on which a certificate of ownership of another party is issued. The results of the study indicate that evidence of Letter C has legal force in court, as long as it can be proven true and supported by other evidence, including documentary evidence, witness statements, confessions of the parties and the results of on-site inspections (descente).